RACISM ASPECT IN GET OUT MOVIE DIRECTED BY JORDAN PEELE - istihayyu buansari; Maulani Pangestu; Fariz Rakha Kans (Pujangga: Jurnal Bahasa dan Sastra, 2021)
The purpose of this research is to determine all aspects of racism in the Get Out film, especially the type of racism, the effects of racism and the type of stereotype. This research used descriptive qualitative method. The data is collected through films that are watched repeatedly and analyzed by the writer and the writer looks for a theory that is in accordance with the observation process from the opinions of experts, journals, books, and social media, then compared with existing opinions. The author uses the theory of Samovar and Maher, well-known researchers who study racism and discrimination. The author found that the racism experienced by Chris Washington in the film Get Out was developed from the beginning to the end of the story. The result of the research film Racism is a belief system or doctrine which states that biological differences inherent in the human race determine cultural or individual attainment - that one race is superior and has the right to rule over another. The results of this study can be concluded that the types of racism are divided into two forms, namely Individual Racism and Micro-Aggression Racism. And also, this research can be concluded that there are two stereotypes of racism, namely discrimination and prejudice.